HARPUT'LU ABDULHAMIT HAMDiEFENDi (1830-1902) VE HZ. PEYGAMBER'iN BILGiSiNE DAiR BiR RiSALESi "Safvetu Efkari'I-Uiema fi isbati Ilmi Nebiyyina bi'I-Esma" - Erul, Bünyamin (Fırat University, 2001)
HARPUTI ABDULHAMİT HAMDİ EFENDi and his epistle "Safwatu Afkari'l Ulama fi Isbliti Ilmi Nabiyyina bi'l-Asma", which is on the Prophet's knowledge: An Ottornan scholar A. Harndi Efendi (1830-1902, from Harput-Elazig) had written a lot ofbooks about Islarnic scienses and the literature. In this work we studied him and his Arabic epistle which was published in 1899, Istanbul, 19 pp. The epistle has three main assertions: 1. The Prophet M uharnrnad had created before the Prophet Adam, 2.Allah had tought him all teachings, as far as had tought Adam all names. 3.The Prophet has knowledge of everything by his soul, even he knows what Allah knows. The author supports these claims with the verses from the Qur'an and a lot of traditions and some sufı poerns. Then, we discussed and examined these assertions in the light of the Prophet's knowledge. W e conclude that, this epistle !ike rnany others, isa tytıical work from our culture and geography about Muslim's misunderstanding of the Prophet. Meanwhile it is an original work in comparison to the first and the last prophets and their knowledges. Morever, it is an important docuınent on Muslim's unlirnited love towards the Prophet It is very interesting to observe that a Muslim scholar occupied himself with such a work at the most difficult time of the Ottornan Empire.
Keywords: Religious Studies; Din Araştırmaları